Способ прогнозирования изностойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Арефьев К. П. Константин Петрович; Галанов Ю. И. Юрий Иванович; Сурков А. С.; Федько В. Т. Валериан Тимофеевич
опубл. 27.04.05